Board Diversity, Sustainability Committee, And Environmental Performance As Determinants Of Carbon Emission Disclosure: Evidence From Indonesian Listed Companies - Rizqy Aiddha Yuniawati; Nafisah Utami Yokachda (Universitas Hayam Wuruk Perbanas, 2026)
This study examines the determinants of carbon emission disclosure among non-financial companies listed in the Top 100 Capitalization market on the Indonesian Stock Exchange (IDX) during the 2020–2024 period. While prior research has yielded mixed findings on the relationship between board characteristics and carbon disclosure, limited evidence exists in the Indonesian context, particularly regarding the combined effects of board diversity, sustainability committees, and environmental performance. Drawing on Stakeholder Theory, Legitimacy Theory, Agency Theory, and Critical Mass Theory, this study employs panel data regression analysis on 80 firm-year observations. The findings reveal that nationality diversity (β = 0.932, p < 0.001) and sustainability committee presence (β = 0.118, p = 0.013) have significant positive effects on carbon emission disclosure. However, gender diversity (p = 0.859) and environmental performance measured by the PROPER rating (p = 0.099) show no significant influence. The model explains 59.1% of the variance in carbon emission disclosure (Adjusted R² = 0.591). This research contributes to the literature by providing empirical evidence from an emerging economy context and offers practical implications for corporate governance policies in Indonesia.